HR Development Perspective On The Economic Growth Of Rural Banks In Indonesia In The Society 5.0 Era - Sunday Ade Sitorus; Anton Atno Parluhutan Sinaga; SUNDAY ADE SITORUS; SUNDAY ADE SITORUS (Journal of Economic, Bussines and Accounting (COSTING), 2024)
One of the banking businesses in Indonesia is Rural Banks requiring tough human resources (HR) with appropriate competence. The activity of managing and developing human resources (HR) is an important and strategic thing in HR management in a Rural Bank (BPR). The purpose of this research are to find the point of skill improvement, competence improvement, human resources' skill transformation into work system , human resources' capability improvement, industry society 5.0-based human resource development and economic growth. This research employed a descriptive quantitative method through path analysis using SPSS 22. The purposive sampling technique, 95 workers of the population were taken using questionnaires distributed via email. The results of this study demonstrated that the improvement of human resources (HR) skills, competence, and skill transformation to the work system positively and significantly affected the increase in HR's capabilities in the Rural Banks throughout Indonesia, and these three variables had an effect on HR development in the Rural Banks based on Industry Society 5.0. Simultaneously, the improvement of HR's skills, competence, and the skill transformation to the work system had a positive and significant impact on HR development based on Industry Society 5.0 in the Rural Banks throughout Indonesia through the increase in HR's capabilities as an intervening variable Keywords: industry society 5.0, human resources, rural banks, development, capability, improvement, economic growth